Implementation of UPFC model into fast decoupled load flow - Mokhlis, Hazlie (IEEE, 2004)
This paper describes the implementation of Unified Power Flow Controller (UPFC) steady-state model into Fast Decoupled load flow analysis. The model is integrated through sequential approach, where equations for solving these devices are separated from the basic Fast Decoupled equations. By using this approach, the basic Fast decoupled algorithm can be added with functionality to analyze UPFC without the need to modify the whole algorithm, which will require minimum modification. The proposed Fast Decoupled load flow has been tested using IEEE data test and shows it effectiveness in solving network containing single or multiple UPFC devices.